The Effects of Gender Interactions in the Lab and in the Field - Antonovics, Kate; Arcidiacono, Peter; Walsh, Randall (The Review of Economics and Statistics, 2009)
An important issue with conducting economic analysis in the lab is whether the results generalize to real-world environments where the stakes and subject pool are considerably different. We examine data from the game show The Weakest Link to determine whether the gender of one's opponent affects performance. We then attempt to replicate the competitive structure of the game show in the lab with an undergraduate subject pool. The results in the lab only match when we both employ high stakes in the lab (≥ $50) and limit our analysis to young contestants in the game show (age < 33).